Produção de filmes de PBAT/PLA por eletrofiação para liberação de nitrofurazona - Megliorini, Leonardo de Souza (2018)
Nitrofurazone is a drug used to treat burns and skin transplants. The drug product is salled in cream and solution form. The ecovio® polymer is composed of poly(lactic acid) / poly(butylene adipate co-teraphtalate) and is biocompatible. In this work a film with the combination of ecovio® and nitrofurazone was produced by the electrospinning technique forming nanofibers. Two films were produced. The first was produced with dimethylformamide / tetrahydrofuran (15:85 v / v) and was capable of releasing 100% of the nitrofurazone reproducibly in the dissolution profile test evaluated for 300 minutes. The second film was produced with dimethylformamide/chloroform (15:85 v/v) and released about 90% of the nitrofurazone. But did not show reproducible results in the same range. Physicalchemical analyzes lead to the conclusion that the interaction of nitrofurazone with the polymer occurs mainly among the more polar groups. The dissolution test was performed following pharmacopoeial parameters. The quantitation of the released nitrofurazone was performed by UV-Vis spectrophotometry at 375 nm. The method used was validated and proved to be adequate, showing linearity in range 0.25 - 12.50 mg.L-1 with correlation coefficient 0.9999, high precision with relative standard deviation ≤ 1.6%, accuracy 98.9 - 100.4%, selectivity and limit of quantification 0.4 mg.L-1.